GROWTH ANALYSIS OF THREE AQUATIC COMMODITIES CULTIVATED WITH POLYCULTURE SYSTEMS AT DIFFERENT DENSITIES - Gawest Bagus Permana; Andi Rahmad Rahim; Aminin Aminin (OJS Universitas Muhammadiyah Gresik, 2021)
Vanamei shrimp and milkfish (Chanos chanos) are now being cultivated in ponds using a polyculture system that is maintained simultaneously in one container. The development of cultivation technology shows that seaweed can be cultivated along with shrimp and milkfish in ponds. With the addition of seaweed is expected to increase production and improve the environmental conditions of cultivation. This polycultural cultivation system can increase the efficiency of land use can also increase the productivity of ponds. This research was conducted in the pond of Glagah Lamongan village for 42 days. This study used milkfish, shrimp vaname and seaweed Gracilaria verrucosa. The research method uses Complete RandomIzed Design (RAL) method with 3 treatments and 3 repeats so that it gets 9 experimental units, the data in the analysis using ANOVA is conducted tukey further tests. Treatment A (density of milkfish and shrimp 10 tails/m2, seaweed 250g/m2), treatment B (density of milkfish and shrimp 20 tails/m2, seaweed 500g/m2), treatment C (density of milkfish and shrimp 30 tails/m2, seaweed 1000g/m2). Variables taken are Absolute Length of milkfish, shrimp vaname and seaweed. The results obtained the absolute length of milkfish, shrimp vaname and seaweed highest in treatment A (7.67 ± 0.54a). Water quality during maintenance, temperature ranges from 29.2 – 32.8oC; DO 1.1-3.4mg/l; Salinity 1-3ppt; brightness range 24 – 50 cm and ground redox obtain a range value of -42-(-328)mV.